Treatment and outcomes of immune cytopenias following solid organ transplant in children. Issue 2 (12th October 2014) - Schoettler, Michelle; Elisofon, Scott A.; Kim, Heung Bae; Blume, Elizabeth D.; Rodig, Nancy; Boyer, Debra; Neufeld, Ellis J.; Grace, Rachael F.
<x xml:space="preserve">Abstract</x> Background Immune cytopenias are a recognized life‐threatening complication following pediatric solid organ transplants (SOT), but treatment responses and overall outcome are not well described. The aim of this study was to evaluate the demographic characteristics, response to treatments, and outcomes of a cohort of patients who developed immune cytopenias following SOT. Procedure In this single center retrospective review, patients with immune cytopenias after SOT were identified by electronic medical record (EMR) search and transplant databases from 1995–2012. Results Of 764 SOT patients, 19 (2.4%) developed immune cytopenias. Incidence varied widely by transplant type from 1.2% (renal) to 23.5% (multivisceral). Autoimmune hemolytic anemia (AIHA) was the most common immune cytopenia. Overall median time from transplant to immune cytopenia was 8 m and varied by transplant type from 3 m (liver) to 74 m (heart). Standard therapies for immune cytopenias were often used and ineffective. The most effective therapy for the immune cytopenia was changing immunosuppression from tacrolimus to another agent. Three of 19 patients died; none directly attributed to the immune cytopenia. Conclusions Immune cytopenias are not rare after SOT, and patients usually do not respond well to traditional first line therapies. Provided that the risk of organ rejection is otherwise manageable, temporary cessation of tacrolimus could be more widely explored in this challenging clinical context. Pediatr Blood Cancer 2015;62:214–218. © 2014 Wiley Periodicals, Inc.